2003
DOI: 10.1001/archinte.163.20.2492
|View full text |Cite
|
Sign up to set email alerts
|

No Door to Lock

Abstract: Sexual and physical assault are common experiences for homeless and marginally housed persons. Housing is associated with lower rates of sexual assault among women. Strategies to decrease sexual and physical assault and its consequences are needed in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(60 citation statements)
references
References 53 publications
4
47
0
2
Order By: Relevance
“…This research has drawn marked associations between sexwork and experiences of violence, life traumas, exploitation and abuse, homelessness, and mental illness (Baker et al, 2001, Potterat et al, 1998). Homelessness in particular exacerbates vulnerability: homeless or marginally-housed FSWs are more likely than FSWs with more stable housing to engage in riskier sexual activities, with a higher risk associated with those with simultaneous drug use (Kushel et al, 2003, Surratt and Inciardi, 2004). …”
Section: Resultsmentioning
confidence: 99%
“…This research has drawn marked associations between sexwork and experiences of violence, life traumas, exploitation and abuse, homelessness, and mental illness (Baker et al, 2001, Potterat et al, 1998). Homelessness in particular exacerbates vulnerability: homeless or marginally-housed FSWs are more likely than FSWs with more stable housing to engage in riskier sexual activities, with a higher risk associated with those with simultaneous drug use (Kushel et al, 2003, Surratt and Inciardi, 2004). …”
Section: Resultsmentioning
confidence: 99%
“…In phase one, the team of four analysts (three of whom were the interviewers) used grounded theory methodologies (Strauss and Corbin, 1990) to construct memo summaries of each interview, which included basic background information, current circumstances, notable events and quotations, and analyst impressions and interpretations. Because previous research (Chan, Dennis, & Funk, 2008; Cohen et al, 2009; Hooper, et al, 1997; Kushel et al, 2003; Luhrmann, 2008) indicated a potential relationship between lifetime histories of traumatic exposure, housing instability, current living situations, and sexual and drug use behaviors, we sought to keep narratives “intact” in the initial data analysis phase. The interview transcript and summaries were then discussed at a 2-hour meeting devoted to analyzing each participant’s interview.…”
Section: Methodsmentioning
confidence: 99%
“…Transwomen, however, are faced with additional hardships associated with homelessness as many are exposed to increased levels of physical, sexual, emotional, and psychological injury due to the increased exposure to transphobia while living in public or while attempting to access services for the unstably housed (Kushel, Evans, Perry, Robertson, & Moss, 2003; Sakamoto, Chin, Chapra, & Ricciardi, 2009). More than half of all transgender persons attempting to access homeless shelter services report harassment by shelter staff and/or residents, almost a third report having been turned away or refused services, and over 20% report having been sexually assaulted by shelter staff and/or residents (Grant et al, 2011).…”
Section: Introductionmentioning
confidence: 99%